2018
DOI: 10.1111/conl.12616
|View full text |Cite
|
Sign up to set email alerts
|

Limited open access in socioecological systems: How do communities deal with environmental unpredictability?

Abstract: Classical theory on the commons holds that rules are fundamental to sustainability. However, open access may be present in many sustainable socioecological systems. Here, we explore the interaction between environmental unpredictability and cooperation in a fishery in the Pantanal wetland, Brazil. We show that a variable annual flood pulse combined with channel blockages results in a high turnover in fishing grounds. To counter this variability, fishers openly share information about fishing areas with all com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 33 publications
(49 reference statements)
0
16
0
1
Order By: Relevance
“…Therefore, between community members, there are no defined boundaries around the resources that they use, as predicted in open property regimes (Moritz et al 2018). We have previously argued that the openness and reciprocity that occurs within the Barra do São Lourenço community is the unpredictable availability of natural resources in the region explained above, which forces people to find cooperative ways to increase their chance of finding fish or bait (Chiaravalloti and Dyble 2019). However, neither information nor fishing grounds are shared with people from outside Barra do São Lourenço (Chiaravalloti 2017a).…”
Section: Governance and Institutional Arrangementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, between community members, there are no defined boundaries around the resources that they use, as predicted in open property regimes (Moritz et al 2018). We have previously argued that the openness and reciprocity that occurs within the Barra do São Lourenço community is the unpredictable availability of natural resources in the region explained above, which forces people to find cooperative ways to increase their chance of finding fish or bait (Chiaravalloti and Dyble 2019). However, neither information nor fishing grounds are shared with people from outside Barra do São Lourenço (Chiaravalloti 2017a).…”
Section: Governance and Institutional Arrangementsmentioning
confidence: 99%
“…Previous studies in the Pantanal have shown that the governance system of fishers from the Barra do São Lourenço community should be classified as a hybrid between open property and common property regimes, named "limited open access" (Chiaravalloti and Dyble 2019). In this system, fishers survive by sharing information about productive fishing or bait gathering locations.…”
Section: Governance and Institutional Arrangementsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in many huntergatherer communities, the majority of hunting trips are unsuccessful, such that individuals rely on social rules that encourage the sharing of food among community members to maintain a regular supply of meat (Gurven, 2004). Similarly, among fishers in the Brazilian Pantanal, social rules facilitating the sharing of information about the location of productive fishing sites are essential for the viability of individual livelihoods (Chiaravalloti & Dyble, 2019). While such social rules facilitating cooperation may be advantageous, they are also vulnerable to "free-riders" who benefit from being part of a cooperative group without contributing to public goods.…”
Section: Introductionmentioning
confidence: 99%
“…While the recent research from Moritz et al (2018) and Chiaravalloti and Dyble (2019) describes socioecological systems that are different from classic property regimes and proposes possible driving conditions that may lead them to exist, there is no attempt understand the importance of rules controlling users' ability to extract/manage natural resources to be sustainable (management rules) and rules facilitating cooperation (social rules). This article aims to further explore these issues, articulate the difference between social and management rules, and explore how social and management rules may interact to produce different kinds of socioecological systems.…”
Section: Introductionmentioning
confidence: 99%